2016
DOI: 10.4236/psych.2016.713157
|View full text |Cite
|
Sign up to set email alerts
|

Differences and Similarities of Mental Health Problems Reported by Adolescents: From Greece, Japan, Russia, and Sweden

Abstract: The aims of the present study were to: 1) compare scores and scales of the Youth Self-Report (YSR) reported by healthy adolescents 15 -17 years of age from Greece, Japan, Russia, and Sweden, 2) analyze gender and age effects of the YSR syndrome scores between and within countries, and 3) compare scores of competence scales and their associations to mental health problems. A comparison of problems (n = 812) yields a small effect size of 4.8% for cross-country in YSR total problems scores. There was a deviation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Finally, Japanese respondents demonstrated a notably different pattern with lower average scores in comparison to the rest of the cultural groups. These findings are consistent with previous findings suggesting that Japanese tend to provide modest self-evaluation and correspondingly lower scores in self-reported studies (Iwata and Buka, 2002 ; Nishikawa et al, 2016 ). However, response biases have also been found within Chinese samples (e.g., Chen et al, 1995 ) and in international samples spanning over 40 distinct countries (Schimmack et al, 2005 ), and yet the lower means emerged only within the Japanese respondents in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, Japanese respondents demonstrated a notably different pattern with lower average scores in comparison to the rest of the cultural groups. These findings are consistent with previous findings suggesting that Japanese tend to provide modest self-evaluation and correspondingly lower scores in self-reported studies (Iwata and Buka, 2002 ; Nishikawa et al, 2016 ). However, response biases have also been found within Chinese samples (e.g., Chen et al, 1995 ) and in international samples spanning over 40 distinct countries (Schimmack et al, 2005 ), and yet the lower means emerged only within the Japanese respondents in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…From a cross‐cultural perspective, it is important to determine whether these differences can be replicated in independent samples. This is particularly so, because in a small‐scale cross‐cultural study, Japanese adolescents rated themselves lower than Russians on the total problems measured by the Youth Self‐Report (Nishikawa et al, 2016). Gender differences in adolescent mental health problems are not consistent across cultures.…”
Section: Body Image and Eating Distressmentioning
confidence: 97%
“…Other studies have demonstrated that ratings of EBPs differ between countries. For example, in a cross-cultural study, Japanese adolescents reported a lower rate of externalizing behaviors (Rule-Breaking and Aggressive Behaviors) than adolescents from Greece, Russia, and Sweden [61]. However, cultural differences might be only one of several reasons for the differences in internalizing versus externalizing problems.…”
Section: Plos Onementioning
confidence: 99%